Passages of Faith : Conversion in Palestinian villages (17th century). - Tramontana, Felicita (Göttinger Orientforschungen. Syriaca., 2014)
The book sets out to explain the diffusion of Catholicism and Islam in the 17th-century district of Jerusalem through a detailed analysis of the changes of faith undergone by the inhabitants of some villages in the area (Dayr Aban,?uba, Bethlehem, Bayt Jala, Bayt Sha?ur and Ayn Karim). The way a new faith spread within and between the local Christian communities was the result of a complex interaction between religious landscape, communal dynamics and individual agency, which the book unravels. Through the stories of the conversions of the Christian villagers, as recorded in contemporary Chris.